IMPLEMENTASI PENDIDIKAN AGAMA ISLAM BERWAWASAN LINGKUNGAN HIDUP MENUJU SEKOLAH ADIWIYATA PADA SISWA KELAS V SDN 1 CLURING BANYUWANGI - Fauzi, Anis; Muttaqin, Ahmad Izza (INCARE, International Journal of Educational Resources, 2022)
This study aims to explain the application of environmental-oriented Islamic education to Adiwiyata schools in class V SDN 1 Cluring, explain the factors of how the implementation of environmental-oriented Islamic education towards Adiwiyata schools, what are the obstacles to implementing environmental-oriented Islamic education towards Adiwiyata schools, what are the obstacles to implementing environmental-oriented Islamic education towards Adiwiyata schools? solutions to obstacles in implementing environmental-friendly Islamic education towards Adiwiyata schools. This research use desciptive qualitative approach. In the process of collecting data using several methods, namely the method of observation, interviews and documentation. The data analysis technique uses qualitative data analysis (data reduction, data presentation and drawing conclusions). As for the results of the study, it can be concluded that the implementation of environmental-oriented Islamic religious education towards Adiwiyata schools in class V of SDN 1 Cluring has been running as it should. It is proven by the existence of programs that are planned and implemented by the school in order to create an atmosphere of a school environment that is culturally environmentally friendly. Among them are good school community behavior, noble character, a clean school environment, tolerance among others, and so on.